Experimental animal study on BMP-3 expression in periodontal tissues in the process of orthodontic tooth movement - Gao, Yang (Exp Ther Med, 2019)
Expression characteristics of bone morphogenetic protein-3 (BMP-3) in the process of orthodontic tooth movement was investigated. Forty-eight rats were randomly divided into the 3-day group (n=12), the 7-day group (n=12), the 14-day group (n=12) and the 21-day group (n=12). The maxillary left molar of each rat was used as the experimental tooth, the orthodontic tooth model was established, and the contralateral molar was used as the control tooth. The tooth movement distance was measured using a vernier caliper at day 1, 3, 7 and 14 after modeling, and rats in each group were sacrificed and sampled at the corresponding time-point. The tissue morphology was observed via hematoxylin and eosin (H&E) staining, and the expression of BMP-3 was detected via immunohistochemistry. The protein expression of BMP-3 was detected via western blotting, and the messenger ribonucleic acid (mRNA) expression of BMP-3 was detected via quantitative polymerase chain reaction (qPCR). At day 14 after modeling, the periodontal space was significantly uneven, the form of periodontal tissues was disordered, and a large number of multinucleated osteoclasts could be seen. The expression levels of BMP-3 in other groups were significantly increased compared with that in the control group (P<0.05). The expression level of BMP-3 reached the peak at day 14 after modeling, and differences were statistically significant compared with those in other time points after modeling (P<0.05). The orthodontic tooth movement distance after modeling was significantly longer with the extension of time (P<0.05). In the process of orthodontic tooth movement, the expression level of BMP-3 is gradually increased and reaches the peak at day 14, promoting the increase of osteoclasts and benefiting the orthodontic tooth movement.